Assessment of photocatalytic capacity of a hydraulic mortar - Castanho, Pedro (2017)
In urban areas façades of buildings and monuments accumulate dirt and are visually degraded, implicating high consumption of resources for repair. The search and development of new products that can help to maintain those façades is therefore very important. To prevent possible damage to the building surface maintaining their aesthetic appearance, cementitious materials with new properties have been developed. One possibility arises from the introduction of titanium dioxide (TiO 2) into the composition of coating materials. When exposed to solar UV radiation, the coatings lead to photo-induced oxidation of compounds adsorbed or deposited on their surfaces, with self-cleaning effect. This self-cleaning property reduces the need for maintenance. In can be an advantage for unpainted renders. In this research, physic-mechanical characterization and evaluation of the self-cleaning capacity of a commercial hydraulic lime mortar with photocatalytic property, by the addition of TiO 2 , were carried out. Two mortars with 1:3 (binder:aggregate) volumetric proportion were produced, only differing on the aggregate type, namely its particle size distribution, and compared with similar mortars but formulated with a common hydraulic lime without TiO 2. In the physic-mechanical characterization mortar specimens were laboratory tested for mechanical strength, open porosity, capillary water absorption and drying capacity. The self-cleaning capacity of mortars was evaluated by monitoring the discolouration of two organic dyes stains (Rhodamine B and Methylene Blue), applied on the surface of mortar specimens, when exposed to sunlight and UV light. The mortars with TiO 2 shown improvements mainly in terms of mechanical strengths but without significant changes concerning water and vapour behaviour. Simultaneously those mortars have shown a great degradation of colour of the two dyes stains, with high colour change percentages particularly after sunlight exposure.